2016
DOI: 10.1021/jacs.6b06683
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Coupled Chloride and Proton Transport in a Cl/H+ Antiporter

Abstract: The ClC family of transmembrane proteins functions throughout nature to control the transport of Cl– ions across biological membranes. ClC-ec1 from Escherichia coli is an antiporter, coupling the transport of Cl– and H+ ions in opposite directions and driven by the concentration gradients of the ions. Despite keen interest in this protein, the molecular mechanism of the Cl–/H+ coupling has not been fully elucidated. Here, we have used multiscale simulation to help identify the essential mechanism of the Cl–/H+… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 45 publications
4
78
0
Order By: Relevance
“…We note that this definition is slightly different than used in our previous work. 35 In that work, we defined a “down” state with a Cl – at S cen for when E148 was rotated to interact with water molecules leading into the pore region, noting that the side chain could not reach as far into the pore as when S cen was not occupied by a chloride ion. That position in the pore corresponds to the lower basin in the region here defined as “up” in panel Figure 5 B.…”
Section: Resultsmentioning
confidence: 99%
“…We note that this definition is slightly different than used in our previous work. 35 In that work, we defined a “down” state with a Cl – at S cen for when E148 was rotated to interact with water molecules leading into the pore region, noting that the side chain could not reach as far into the pore as when S cen was not occupied by a chloride ion. That position in the pore corresponds to the lower basin in the region here defined as “up” in panel Figure 5 B.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental biophysicists have shown that these mechanisms are complex, involving interdependent influences of transmembrane voltage, [Cl − ], and [H + ] [8,[32][33][34][35][36]. To begin to resolve these complexities and reveal the dynamic, atomistic details of the CLC gating machine, it will be critical to pair structural studies with high-resolution conformational modeling [37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The MS-RMD models are developed from and calibrated against QM/MM data by utilizing a force matching algorithm in a "machine learning" type methodology. The MS-RMD approach can efficiently and accurately simulate explicit PT in proteins, as mediated by water molecules and amino acids while including Grotthuss proton shuttling, see, e.g., refs (34)(35)(36)(41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%